2015
DOI: 10.1007/s40262-015-0329-4
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Lanreotide Autogel®/Depot in the Treatment of Neuroendocrine Tumors: Pooled Analysis of Four Clinical Trials

Abstract: Using two mechanisms of absorption, the pharmacokinetics of lanreotide Autogel were well-described in patients with GEP-NET. None of the patient characteristics tested were of clinical relevance to potential dose adjustment in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…1b successfully described LAN time profiles, CgA dynamics, and PFS. LAN concentrations were adequately described by the population PK model (23). The estimated half-life of LAN was 0.59 h, and the model predicted trough (predose) value (2.5th-97.5th prediction intervals corresponding to the 120-mg dose administered subcutaneously every 4 weeks) was 6 (3-11) ng/mL.…”
Section: Model Evaluationmentioning
confidence: 92%
See 2 more Smart Citations
“…1b successfully described LAN time profiles, CgA dynamics, and PFS. LAN concentrations were adequately described by the population PK model (23). The estimated half-life of LAN was 0.59 h, and the model predicted trough (predose) value (2.5th-97.5th prediction intervals corresponding to the 120-mg dose administered subcutaneously every 4 weeks) was 6 (3-11) ng/mL.…”
Section: Model Evaluationmentioning
confidence: 92%
“…The LAN pharmacokinetic properties were characterized as part of a pooled analysis of four clinical trial including patients with functioning and nonfunctioning GEP-NETs (23). The popPK model selected consisted on a onecompartment disposition model with an absorption process characterized by two parallel absorption pathways, following first-and zero-order kinetics, and was used to predict the corresponding serum profiles in LAN to develop the models for CgA dynamics and PFS using the model parameters represented in Supplementary Table S1.…”
Section: Lanreotide Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of any other systemic therapy could be ruled out since these patients were not included. In addition, from in vitro studies it is known that SSA inhibits cell growth within a short period of time and pharmacokinetic studies with humans revealed similar results [47, 48]. A control collective would be desirable.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption model used to estimate the corresponding absorption parameters allowing afterwards computation of metrics is represented in the work from [ 3 ] and comprises three non-simultaneous absorption mechanisms, two of them following 1 st order kinetics and the third one following a 0 th order process. This model is considered of a sufficient complexity to deal with almost any absorption profile that can take place after administration of SR formulations [ 16 , 17 ]. A schematic representation of the structural model with the corresponding ordinary differential equations is provided in S1 Fig .…”
Section: Methodsmentioning
confidence: 99%